Pendampingan Remaja Dalam Meningkatkan Pengetahuan Dan Sikap Pencegahan HIV/AIDS Di Daerah Pesisir Kabupaten Sumenep - Hadina Eka Camalia; Dian Permatasari; Emdat Suprayitno; Sri Yunita Suraida Salat (Jurnal Empathy Pengabdian Kepada Masyarakat, 2021)
Background: Human Immunodeficiency Virus (HIV) or Acquired Immunodeficiency Syndrome (AIDS) is a growing health problem in Indonesia. From 1987 to 2019, there were 102,667 AIDS sufferers. Adolescents aged 15-24 years are a group that is vulnerable to HIV. The purpose of PKM is for universities to play a role in developing public knowledge about reproductive health and the spread of HIV/AIDS among adolescents infection. Adolescents are a group that is more likely to transmit HIV/AIDS because they are vulnerable to risky behavior problems, such as premarital sex and substance abuse. Methods: The target of service is youth in coastal areas. Problems are solved in three stages of activity, namely preparation, implementation and evaluation. Preparation is done by conducting a preliminary survey to see conditions in the field. The implementation is carried out by training, using the lecture method, namely the presentation technique, followed by question and answer discussions and exercises as a form of PKM activities. Evaluation of activities is carried out for each stage by collecting and concluding data from each stage of activity. Results: Before distributing 24 questionnaires containing information about adolescent reproductive function and HIV/AIDS to counseling participants, the result was 65%. Meanwhile, from the results of a survey of all participants to assess expansion achievement, it was found that 84%. A significant increase in participants' knowledge was 18%. Conclusion: By providing knowledge to parents, we can reach youth to avoid problems related to HIV/AIDS.